2020
DOI: 10.2147/prbm.s238063
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Joint Influence of Online Rating and Product Price on Purchase Decision: An EEG Study</p>

Abstract: Background: Consumers had to encounter and consider product-oriented and revieworiented cues before making an online purchasing decision. It was important to resolve how these cues influenced consumers' online purchasing decision. We also knew little about how the human brain processed these cues simultaneously, and which cue would occupy a dominant position in neural activity. The purpose of the present study was to investigate the neural correlates of online shopping decisions and how online rating and produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 40 publications
1
9
0
3
Order By: Relevance
“…Although recent research has shown that conscientiousness, too, predicts impulse buying [77], our study did not reveal effects of this dimension. The buying impulsiveness also had direct effects on the buying intention in the context of online buying, as other researchers had previously demonstrated [78].…”
Section: Theoretical Implicationssupporting
confidence: 59%
See 1 more Smart Citation
“…Although recent research has shown that conscientiousness, too, predicts impulse buying [77], our study did not reveal effects of this dimension. The buying impulsiveness also had direct effects on the buying intention in the context of online buying, as other researchers had previously demonstrated [78].…”
Section: Theoretical Implicationssupporting
confidence: 59%
“…Being only a hypothetical situation, the responses for the self-report measures could be biased. In a real-life situation, price and also product rating could have major impacts on the buying decision [78].…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
“…Research in consumer psychology demonstrated a probable relationship between N2 and perceived risk because risk and conflict are interrelated (Folstein and Van Petten, 2008;Spapé et al, 2011;Larson et al, 2012;Ma et al, 2015;Wang et al, 2016). Compared with products with high review ratings, those with low ratings evoked greater perceived decision risk, resulting in a larger N2 amplitude.…”
Section: Discussionmentioning
confidence: 99%
“…Penelitian Venessa & Arifin (2017) menyatakan bahwa pengaruh harga pada keputusan pembelian berpengaruh positif dan signifikan. Penelitian Bairizki (2017), Albari (2020), Hanaysha (2018), Sun et al (2020) juga menyatakan bahwa pengaruh harga pada keputusan pembelian berpengaruh positif dan signifikan. Tetapi berbeda dengan penelitian Mahanani (2018) dan Puspitasari et al (2017) yang menyatakan bahwa harga berpengaruh negatif terhadap keputusan pembelian.…”
Section: Kerangka DI Atas Diambil Berdasarkan Judul Penelitian Pengaruh Harga Citraunclassified